Analysis of Views on Digitalization of Design Studios - Akyıldız, Nihal Arda; Ekici, Betül Bektaş; Karabatak, Songül; Alanoğlu, Müslim (My University, 2023)
Design studios, one of the most important components of architectural education had to move to digital environments urgently and independent of space with the Covid-19 pandemic. This study aims to evaluate whether design studios can be digitized according to the views of students and instructors in two different architecture schools (Firat and Balikesir University) by considering this compulsory experience. The views of 71 students and 5 academicians were taken with a purposeful sampling method. Content and descriptive analyses were performed on the views collected from the participants. As a result, the biggest problem in moving design studios to a digital environment is the disappearance of physical environments in which collaboration, idea sharing, and discussions will occur. In addition, the advantages of online education continued their attraction for some students in the digitalization of design studios. In terms of instructors, games, simulations, modeling, and virtual reality can be used for successful digital studio applications and the infrastructures of these applications can be improved with support from mobile devices.
Keywords: Architecture education; face-to-face education; Design studio; digital design studio